FAKTOR-FATOR YANG MEMPENGARUHI TERJADINYA URBANISASI DI PROVINSI BALI - I Gede Ketut Suntajaya (PIRAMIDA, 2014)
Bali experienced a relatively rapid urbanization. This can be seen from an increasing proportion of the urbanpopulation during the last 30 years i.e. from 14.7 percent (the Population Census of 1980) to more than 60.0percent (the Population Census of 2010). In the future, the demographers estimate that the process of urbanizationin Indonesia is more likely due to the rural-urban migration. This estimate is based on the increasingly low naturalgrowth of urban population, the relatively slow pace of change in the status of rural into urban areas, and therelatively strong economic and development policies that tend to “urban bias”. The latter increase the attractivenessof urban areas for people who live in rural areas.This study aims to determine the factors that influence the occurrence of migration from rural to the urban areasin Bali. Data were collected from 300 sample respondents that distributed proportionally in each regency / city inaccordance with the proportion of the urban population in each region under studied. The samples of respondentswere urban people who came from rural areas outside Bali, or from the regencies of Bali who migrated within aperiod of 2010-2014. Samples were taken by accidental and descriptive data analysis with reference to the table offrequency distribution.The findings show that the main push factor in the area of origin that causes a person to take rural-urbanmigration, as many as 77.4 percent of respondents mentioned it was because of economic incentives, 17.3 percent dueto social factors, and 5.3 percent mentioned that the traditional custom practices in the area of origin are relativelyburdensome. While the pull factors in destination areas were similar, namely economic factors mentioned by 70.0percent of respondents, social factors expressed by 18.3 percent, and as many as 11.7 percent of respondents arguedthat the traditional custom practices are less burdensome in the urban areas.